Víctimas del desplazamiento forzado, frente a la atención humanitaria en el punto de atención de Chapinero - Bogotá, D.C. (2019)
In Colombia different victimizing facts have been presented, within them are those generated by violent groups, attacking different populations with the consequent forced displacement, violating their fundamental rights, fomenting states of absolute poverty and psychosocial affectation. Therefore, the Colombian State in search of compensation for the damage generated by these events and reestablishing their rights implements norms, providing during the process, humanitarian attention to guarantee their minimum maintenance, which entails to investigate if this population actually uses and enjoys of their rights according to what is established in the current regulations, for which surveys are carried out on a sample of 34 displaced persons who attend the Victims Unit at the Chapinero service point in the city of Bogotá, DC where it is possible to demonstrate the nonconformity on the part of those affected, its revictimization due to the lack of real presence of the state as guarantor of their rights.